(3GddeYI GdOeTbjIs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s
(3ChdgG (B:s
(3eHJhQI GdChd, hChd GdehLhO bhdg(B: (3hjSJMH GdLdhS aj eUdGgG HYO GdhVhA hjPcQ Gddg HbOQ GdUdGI(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efg ef cJGH GdbUGU (B: (3ajg eSGFd(B: (3dh CcQg (B...(3Ydi GdbJd aGdbUGU Ydis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B109s
(3GdPQjYI(B:(3L(B18(3,U(B367(3,Qbe(B440s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis